2022
DOI: 10.3390/pathogens11091062
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Veterinary Antibiotics via Food Chain Disrupts Gut Microbiota and Drives Increased Escherichia coli Virulence and Drug Resistance in Young Adults

Abstract: Exposure to veterinary antibiotics (VAs) and preferred as veterinary antibiotics (PVAs) via the food chain is unavoidable for their extensive use not only for treating bacterial infections, but also for use as growth promoters in livestock and aquaculture. One of the consequences is the disturbance of gut microbiota. However, its impact on the virulence and drug resistance of opportunistic pathogens is still unclear. In this study, a total of 26 antibiotics were detected in the urine of 300 young undergraduate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…For a long time, antibiotics has played a positive role in improving the growth performance of broilers, reducing the incidence of diseases, and improving gut health [ 3 ]. However, the long-term use of antibiotics has led to problems such as drug resistance, which has a serious impact on global public health [ 4 , 5 , 6 ]. The ban on antibiotics in feed has forced people to look for new antibiotic alternatives to ensure the healthy growth of broilers.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, antibiotics has played a positive role in improving the growth performance of broilers, reducing the incidence of diseases, and improving gut health [ 3 ]. However, the long-term use of antibiotics has led to problems such as drug resistance, which has a serious impact on global public health [ 4 , 5 , 6 ]. The ban on antibiotics in feed has forced people to look for new antibiotic alternatives to ensure the healthy growth of broilers.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method leads to the emergence of residual antibiotics and multiple foodborne drug-resistant bacteria in the food chain, posing a serious threat to food safety ( Liao et al, 2020 ; Thapa et al, 2020 ). Various foodborne bacteria, such as Escherichia coli (MDR) ( Liu et al, 2022 ), Staphylococcus aureus (MRSA) ( Algammal et al, 2020 ), Salmonella enterica serovar Rissen ( Xu et al, 2020 ) and Listeria monocytogenes ( Baquero et al, 2020 ), have been reported to exhibit drug resistance. These bacteria have evolved multiple mechanisms, including reduced cell membrane permeability, efflux pump mechanisms, target site mutation mechanisms, and enzymatic hydrolysis, to cope with antibiotics ( Ge et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Problems with drug resistance and residues in livestock products have resulted in the recent ban of antibiotic use in livestock and poultry breeding in several countries ( Liu et al, 2020 ). Therefore, it is important to identify and evaluate alternatives to antibiotics, including “green additives”.…”
Section: Introductionmentioning
confidence: 99%